Knowledge Sharing In Improving Police Human Resources (Study On Police Language School) - Ningrum, Rina Widya; Atmoko, Andreo Wahyudi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Knowledge sharing is an important element in human resource development in the contemporary era. Sebasa Polri, as a language education institution for police officers, requires a knowledge sharing strategy to improve coordination of student recruitment, competence of teaching staff, and optimization of student placement after education. This study aims to analyze the implementation of knowledge sharing with the SECI model at Sebasa Polri. The research method uses a literature study with secondary data sources from academic journals, publications, and other relevant sources. The results show that the implementation of the SECI model can increase the effectiveness of coordination and knowledge sharing, but its implementation has challenges in terms of coordination, collaboration in improving learning, and post-education evaluation systems. The implications of this research focus on the need for a structured strategy within Sebasa Polri to support the implementation of more integrated and adaptive knowledge sharing.